(untitled) (International Nexus Multidisciplinary Research Journal, 2026)
Calcium carbide is widely used in fruit ripening but its waste poses environmental risks when it enters agricultural soils. This study investigated the effects of different concentrations of calcium carbide (0%, 0.5%, 1.0%, 2.0%, and 5.0% w/w) on the physicochemical and microbiological properties of loamy agricultural soil from the Owerri, Imo State. Soil samples were incubated for 30 days under controlled laboratory conditions. Results showed a significant dose-dependent increase in soil pH (from 6.45 to 8.67) and electrical conductivity, alongside increases in available phosphorus and exchangeable calcium. However, organic carbon, total nitrogen, and exchangeable potassium declined. Total heterotrophic bacteria, fungi, and actinomycetes counts decreased drastically, with near-complete suppression of fungi at 5.0% carbide. These findings indicate that calcium carbide alters soil chemistry and exerts strong antimicrobial effects, potentially impairing soil fertility and microbial ecosystem functions. Strict regulation of carbide waste disposal and adoption of safer alternatives are recommended.